The art of making clothing fabric in ancient Iraq (Linen and cotton) as an example (Journal of the College of Basic Education, 2024)
Much of the evidence that has been uncovered in all parts of the earth indicates that for a long time, man lived by gathering and hunting, and this confirms that the animals he hunted used their skin, fur, or wool as a cover to protect him from the cold of winter, in addition to using clothing for his body to protect him from the elements. Different nature. Before he knew about agriculture and domesticating animals, man was dependent on nature, which provided him with food. He had hardly learned agriculture and was guided to domesticate animals until the wheel of development turned and began to spread to all aspects of life, as the first agricultural societies appeared and the political, economic, and industrial developments that followed them laid the foundation stone for the emergence of civilized society. The stable.Civilized society has relied on its energies to provide its food and clothing, and has conveyed its experience to us in various artistic ways, the effects of which remain immortal to the present day. Cultural and artistic wealth has been transferred from generation to generation by linking the present with the past. Moreover, it is possible for the viewer to receive much of what the richness of civilization offers and whoever does not. He does not understand the civil development that was built on foundations whose components were planning, architecture, and human history, including art, literature, and poetry, including “belief, knowledge, values, and law, as well as” any ability or habit that a person acquires in his society, expressed in material achievements and what they symbolize, distributed over Population settlements represented by cities, which constitute a “common” product between them, are distinguished from one another by their characteristics and heritage from others.From here came this study of man’s knowledge of the art of making raw materials for clothing, which come from plants (linen and cotton). Being plant materials, they were not ready-made as in leather and fur. Rather, working on them required “ardent thought,” “artistic” work, and skilled hands for the complete formation, and she gave us some texts. The studied cuneiforms are artistic images expressing the lives of the people in ancient Iraq, their ways of living, their professions, and their interests. The art of making raw materials for clothing is considered a “wide” art and has taken up a “large” space due to its importance in the life of society and its religious, social, and cultural connotations.